Oncogenic events regulating tissue factor expression (Hematology Meeting Reports, 2009)
Tissue factor (TF) is the primary cellular initiator of blood coagulation and a modulator of angiogenesis and metastasis in cancer. Indeed, systemic hypercoagulability (Trousseau sign) in cancer patients and TF overexpression by cancer cells are both closely associated with disease progression, but their respective causes have long been elusive. We have previously hypothesized1 and recently demonstrated experimentally 2;3 that upregulation of TF expression in cancer is controlled in a qualitatively different manner than in other procoagulant processes, notably by cancer-associated oncogenic events, such as activation of K-ras and epidermal growth factor receptor (EGFR) or inactivation of p53 tumor suppressor gene. These respective transforming alterations exert their impact on both, cell-associated and soluble/circulating (microvesicle- associated) TF expression and activity. TF expression is also an important effector of the K-ras–dependent tumorigenic and angiogenic phenotype of colorectal cancer cells in vivo. Thus, a causal link may exist between genetic tumor progression, angiogenesis and cancer coagulopathy,1;4;5 and TF appears to be an important common denominator in these processes.1;3;6-8